Accounting for foreign exchange operations and its implications for monetary policy implementation: international experience and the case of Brazil - Scalco Macalos, Joao Pedro (Brazilian Keynesian Review, 2020)
Central banks play a unique role in the payment systems and in the issuance of their currencies. Therefore, they cannot become illiquid. However, persistent losses can undermine their credibility. The law 11,803 diminished the possibility of negative results at the Brazilian Central Bank (BCB) by isolating and transferring its foreign exchange results to the Treasury. It also created an asymmetrical distribution scheme that automatically supplies the BCB with the necessary bonds to execute its liquidity management operations and assured the accounting hedge of the foreign exchange swaps, enhancing its autonomy. The main drawbacks of this legislation are the lack of transparency and the increased frequency of transfers between the BCB and the Treasury. However, the expansion of the reverse repos is tied to the accumulation of international reserves and to the interest rate differential between foreign assets and local liabilities and would have happened regardless of the monetary policy instrument.